An assessment of the haemodynamic alterations in acute myocardial infarction using the systolic time intervals. Issue 6 (November 1971) - Bennett, E. David; Smithen, Charles S.; Sowton, Edgar
Abstract : Systolic time intervals were measured in 24 patients with acute myocardial infarction and compared to normal values predicted for heart rate and sex. Pulmonary artery pressures were measured in 18 patients and cardiac outputs using the Fick technique in 10 patients. In all patients the QS2 interval (total electromechanical systole) was short during the acute episode. This shortening in the QS2 interval was due primarily to a reduction in left ventricular ejection time (r=0·71; P<0·001) with no change in the pre-ejection period. The mean deviation from normal of the QS2 interval was 27 ± 3·6 msec in patients with an uncomplicated clinical course and 52 ± 4·7 msec in patients with a complicated course, the difference being significant at the 1% level. Those patients with the highest pulmonary artery diastolic pressure tended to have the shortest QS2 intervals (r=−0·58; P<0·01). There was no relationship between stroke volume and the deviations in the QS2 and left ventricular ejection time intervals from normal. The implication of these findings is discussed.